Medusae, siphonophores and ctenophores of the Magellan Region - Pagès, Francesc; Orejas, Covadonga (Scientia Marina, 1999)
Medusae, siphonophores and ctenophores were conspicuous and relatively abundant organisms in the Magellan Straits, Beagle Channel and adjacent waters during the "Victor Hensen" campaign in 1994. Hydromedusae were the most abundant component of this assemblage (mainly Bougainvillia macloviana, Clytia simplex and Obelia spp.) and showed the highest number of species (29). Siphonophores were second in species number (8) and mainly occurred outside the Magellan Straits (mainly Muggiaea atlantica, Dimophyes arctica, Lensia conoidea and Pyrostephos vanhoeffeni). Callianira antarctica was the only mesozooplanktonic ctenophore and showed a widespread distribution throughout the region. Aggregations of large Beroe cucumis and Desmonema gaudichaudi were observed at some stations. The abundance and depth distribution is given for the most important species and some patterns in the species distribution are postulated Peer reviewed